AN ANALYSIS OF FLOUTING OF MAXIM PERFORMED BY POLITICIAN GUESTS IN MATA NAJWA TALK SHOW IN THE EPISODE OF ADU LANTANG JELANG PENENTUAN AND BABAK AKHIR PILPRES - Norin Aisya; Fitrawati Fitrawati (Universitas Negeri Padang, 2019)
In the process of communication, speakers are expected to obey the maxim of cooperative principles to convey messages effectively. However, many speakers disobey it for some reasons. Flouting of maxim is one of cases when speakers fail to observe the maxim to generate an implicature. This research aimed to find the types of flouting of maxim and the reasons of indirectness in flouting the maxim done by Politician guests in two episode of Mata Najwa Talk Show named Adu Lantang Jelang Penentuan and Babak Akhir Pilpres. The method of this research is descriptive research . The data of this research were the utterances of guests that flout the maxim of cooperative principles. It is found that there were total of 55 utterances that flout the maxim of cooperative principles that were analyzed. The results show that the Politician guests flout maxim of quantity and manner the most with frequency of 53.96% and 36.50%. Flouting of maxim of quality and relation rarely appeared with the same frequency, 4.76%. It is also found that the reasons of indirectness in flouting the maxim were vary such as interestingness, increasing the force’s of messages, competing goals, and politeness. However, increasing the force of the messages and politeness are two reasons that occurred more frequent in comparison with interestingness and competing goals. This research implicated that politician guests convey messages by flouting maxim for many reasons in order to gain support from masses.